Dewi Kilisuci Figure; Disaster Mitigation in the Ecofeminism Perspective - Setiawati, Eti; Rizal, Maulfi Syaiful; Budiarti, Nadhea Arnisma (Humaniora: Journal of Indonesia Culture and Society, 2022)
The research focused on the efforts of the Mount Kelud community in disaster mitigation from the perspective of the story of Dewi Kilisuci, one of the central figures of the legend of Mount Kelud. Ecofeminism viewed that nature as a symbol of women. Mitigation efforts could be carried out through the societyâ€™s cultural wisdom by carrying out various traditional ceremonies. The ceremony would be closely related to various legendary figures that the community believes. In addition, it could also be done through symbolic efforts. The research applied a qualitative descriptive research method. Data were obtained through interviews as well as content analysis, and descriptive analysis techniques used to explain stories and disaster mitigation efforts of societyâ€™s cultural wisdom based on symbolic ecofeminism. It is found that the story of the character of Dewi Kilisuci, where there are mitigation efforts carried out symbolically by her character, which until now is believed by the people. It also explains the role, value, and position of the figure of Dewi Kilisuci as a symbol of women in relation to ecofeminism. It is hoped that the research will be able to provide an understanding of the local cultural wisdom of the community and disaster mitigation efforts and find out how natural values are related to women.Â